2019
DOI: 10.1002/ecy.2863
|View full text |Cite
|
Sign up to set email alerts
|

SupportingSpartina: Interdisciplinary perspective showsSpartinaas a distinct solid genus

Abstract: In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus, including (among others) species previously included in the genera Spartina, Calamovilfa, and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 72 publications
(116 reference statements)
0
22
0
Order By: Relevance
“…All sites contained salt marshes strongly dominated by salt marsh/smooth cordgrass, Sporobolus alterniflorus (Loiseleur) P.M. Peterson and Saarela (Weakley ). We note that nomenclature of this grass, previously Spartina alterniflora Loiseleur, based on molecular data (Peterson et al , b), has remained contentious based on long use of Spartina to designate this group of often dominant grasses in marsh ecosystems (Bortolus et al ). Within each site, we established two 20 m transects (separated by 5 m) that extended into marsh vegetation from the edge of open water (Adams et al ).…”
Section: Methodsmentioning
confidence: 99%
“…All sites contained salt marshes strongly dominated by salt marsh/smooth cordgrass, Sporobolus alterniflorus (Loiseleur) P.M. Peterson and Saarela (Weakley ). We note that nomenclature of this grass, previously Spartina alterniflora Loiseleur, based on molecular data (Peterson et al , b), has remained contentious based on long use of Spartina to designate this group of often dominant grasses in marsh ecosystems (Bortolus et al ). Within each site, we established two 20 m transects (separated by 5 m) that extended into marsh vegetation from the edge of open water (Adams et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The Spartina spp. (cordgrass) (Bortolus et al, 2019) greatly alter brackish and estuarine salt marsh environments via changes in the sediment properties of the tidal flats with growth, resulting in its subsequent further population expansion (e.g., Howes and Teal, 1994;Neira et al, 2005). In addition, serious ecological impacts of Spartina species on native aquatic ecosystems through competitive exclusion (Goss-Custard and Moser, 1988;Wan et al, 2009;Zhou et al, 2009;Morgan and Systma, 2010) and changes in community and trophic structures (Simenstad and Thom, 1995;Levin et al, 2006;Bortolus et al, 2015) were found due to their expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Spartina alterniflora, a perennial salt-tolerant plant, originated from the west coast of the Atlantic and the Gulf of Mexico, and it is the dominant plant in the low salt marsh of the coastal zone (Bortolus et al, 2019;Bortolus, Carlton & Schwindt, 2015;Peterson et al, 2014). S. alterniflora plays an important ecological role in the country of origin.…”
Section: Introductionmentioning
confidence: 99%